(untitled) (Filološke pripombe, 2019)
This text is about the verbal components of rituals with masks. Ceremonies with masks are not pure forms of speech; they contain a combination of games and acts. In this way, the speech and acts have a monologue or dialogue form; in addition, they may be prose or poetry. In ceremonies with masks the words are followed by gestures or presented in a form of action by the group showing the effects of the divided roles, with or without a mask, but with undoubted effects. They can follow the development of national language and speech of syncretic forms from symbolic magical formulas to the final phase of everyday speech. Such development of speech in the ceremonies with masks has its roots in the development of texts in the popular drama, because there is a large number of relations that connect the folklore drama with this folk performance. The texts in the ceremonies with masks can be both improvised and fixed. It is usually fixed when it is in verses, and when in prose it is often subject to change and improvisation by the artists. The creation of the texts is influenced by the space where the ritual is performed, which is most often open space - the center of a city or village, courtyard of a household, and its proximity with the audience. The dialogue here is closer to everyday conversation than the conventions of drama texts, because the performers are neither professional actors nor writers of plays.